Optimizing donor selection for public cord blood banking: influence of maternal, infant, and collection characteristics on cord blood unit quality. Issue 2 (27th May 2013) - Page, Kristin M.; Mendizabal, Adam; Betz‐Stablein, Brigid; Wease, Stephen; Shoulars, Kevin; Gentry, Tracy; Prasad, Vinod K.; Sun, Jessica; Carter, Shelly; Balber, Andrew E.; Kurtzberg, Joanne
<x xml:space="preserve">Abstract</x> Background Banked unrelated donor umbilical cord blood (CB) has improved access to hematopoietic stem cell transplantation for patients without a suitably matched donor. In a resource‐limited environment, ensuring that the public inventory is enriched with high‐quality cord blood units (CBUs) addressing the needs of a diverse group of patients is a priority. Identification of donor characteristics correlating with higher CBU quality could guide operational strategies to increase the yield of banked high‐quality CBUs. Study Design and Methods Characteristics of 5267 CBUs donated to the Carolinas Cord Blood Bank, a public bank participating in the National Cord Blood Inventory, were retrospectively analyzed. Eligible CBUs, collected by trained personnel, were processed using standard procedures. Routine quality and potency metrics (postprocessing total nucleated cell count [post‐TNCC], CD34+, colony‐forming units [CFUs]) were correlated with maternal, infant, and collection characteristics. Results High‐quality CBUs were defined as those with higher post‐TNCC (>1.25 × 109) with CD34+ and CFUs in the upper quartile. Factors associated with higher CD34+ or CFU content included a shorter interval from collection to processing (<10 hr), younger gestational age (34‐37 weeks; CD34+ and CFUs), Caucasian race, higher birthweight (>3500 g), and larger collection volumes (>80 mL). Conclusions We describe characteristics identifying high‐quality CBUs, which can be used to inform strategies for CBU collection for public banks. Efforts should be made to prioritize collections from larger babies born before 38 weeks of gestation. CBUs should be rapidly transported to the processing laboratory. The lower quality of CBUs from non‐Caucasian donors highlights the challenges of building a racially diverse public CB inventory.